Method for producing olefin polymer
Patent Information
- Application Number
- JP2020144796
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-28
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2040-08-28
AI Technical Summary
【0013】 本発明にかかるオレフィン系重合体の製造方法によれば、重合器壁や撹拌翼等の重合器内部の汚れを防止し、かつ、製造装置の運転の安定性と重合活性の更なる向上を達成することができる。
Smart Images

Figure 0007610375000001 
Figure 0007610375000002 
Figure 0007610375000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an olefin polymer, which can prevent fouling of the inside of a polymerization vessel, such as the walls of the polymerization vessel or the stirring blades, and can achieve further improvements in the stability and polymerization activity during the operation of the production apparatus. [Background technology]
[0002] In chemical plants such as petroleum distillation and refining plants and polyolefin manufacturing plants, problems such as a drop in the heat exchange capacity of the plant and blockage of piping can occur due to fouling, which can result in unstable production operations and, in the worst case, operation shutdown. Specific problems that are known include, for example, the generation of polymer lumps or sheet-like matter in a polymerization vessel and the adhesion of polymer to the stirring blades and walls of the polymerization vessel.
[0003] As a method for solving these problems, Patent Document 1 discloses a method of adding an alkyldiethanolamine compound to a polymerization vessel in which olefin polymerization is performed by a gas phase method using a solid catalyst. Furthermore, Patent Document 2 discloses a method for producing an olefin polymer using an antistatic agent-containing prepolymerization catalyst obtained by contacting an antistatic agent with a prepolymerization catalyst obtained by prepolymerizing an olefin in the presence of a solid catalyst, and then prepolymerizing the olefin again. Patent Document 2 discloses that (C-1) polyalkylene oxide block, (C-2) higher aliphatic amide, (C-3) polyalkylene oxide, (C-4) polyalkylene oxide alkyl ether, and (C-5) alkyldiethanolamine can be used as the antistatic agent. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2000-313718 A [Patent Document 2] JP 2001-048912 A Summary of the Invention [Problem to be solved by the invention]
[0005] Olefin polymers are important industrial products that are widely used in a wide variety of applications, and further improvement in their productivity is desired. An object of the present invention is to provide a method for producing an olefin polymer, which can prevent fouling of the inside of a polymerization vessel, such as the walls of the polymerization vessel or the stirring blades, and can achieve further improvement in the operational stability and polymerization activity of the production apparatus. [Means for solving the problem]
[0006] The present inventors have found that, in order to further improve the productivity of olefin polymers, when olefins are polymerized in the presence of a solid catalyst, a polyoxyethylene alkylamine compound and a polyalkylene oxide block compound are specially selected and combined as antistatic agents and fed to a polymerization vessel, thereby preventing fouling of the inside of the polymerization vessel, such as the walls of the polymerization vessel and the stirring blades, and further improving the stability of operation of the production apparatus and the polymerization activity. The present invention has been made based on this new finding by the present inventors. The gist of the present invention is as follows.
[0007] [1] In the presence of (A) a solid catalyst component for olefin polymerization, (B) a polyoxyethylene alkylamine compound represented by the following general formula (I), and (C) a polyalkylene oxide block compound represented by the following general formula (II), A method for producing an olefin polymer, comprising (co)polymerizing ethylene and one or more olefins selected from the group consisting of α-olefins having 3 to 20 carbon atoms in a polymerization vessel.
[0008] [ka]
[0009] [In the above general formula (I), R is a hydrocarbon group having 1 to 30 carbon atoms, and m and n are each independently an integer of 1 or more.]
[0010] [ka]
[0011] [In the above general formula (II), a represents 1 to 20, b represents 1 to 50, and c represents 1 to 20.]
[0012] [2] The method for producing an olefin polymer according to [1], wherein a mixture of components (B) and (C) and component (A) are separately added to a polymerization vessel. [3] The method for producing an olefin polymer according to [1], further comprising contacting a mixture of the components (B) and (C) with the component (A) to obtain a preparation, and supplying the preparation to a polymerization vessel. [4] The method for producing an olefin polymer according to [1], comprising: supplying a preparation obtained by contacting a mixture of component (B) and component (C) with component (A) to a polymerization vessel; and further supplying a mixture of component (B) and component (C) to the polymerization vessel. [5] The method for producing an olefin polymer according to any one of [1] to [4], wherein the (co)polymerization of an olefin is carried out in a suspension or in a gas phase. [6] Component (A) is (A-1) a transition metal compound of Group 4 of the periodic table having a cyclopentadienyl skeleton; (A-2) at least one compound selected from the group consisting of (a) organometallic compounds, (b) organoaluminum oxy-compounds, and (c) compounds that react with component (A-1) to form an ion pair; (A-3) a fine particle carrier; The method for producing an olefin polymer according to any one of [1] to [5], comprising: Effect of the Invention
[0013] According to the process for producing an olefin polymer of the present invention, it is possible to prevent fouling of the inside of a polymerization vessel, such as the walls of the polymerization vessel or the stirring blades, and to achieve further improvements in the operational stability and polymerization activity of the production apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] [Solid catalyst component for olefin polymerization (A)] The solid catalyst component (A) for olefin polymerization [component (A)] is preferably, for example, a solid catalyst component containing a compound of a transition metal selected from Groups 3 to 12 of the periodic table. Specific examples thereof include a support-supported transition metal complex catalyst component in which a transition metal compound of Groups 4 to 6 of the periodic table is supported on a particulate support, a solid titanium catalyst component containing a solid titanium catalyst component and an organoaluminum compound, and a Phillips catalyst component in which any chromium compound that can be oxidized to chromium trioxide is supported on an inorganic oxide solid such as silica.
[0015] The transition metal compound of Groups 4 to 6 of the periodic table used in the carrier-supported transition metal complex catalyst component may be any known transition metal compound of Groups 4 to 6 of the periodic table having olefin polymerization ability. For example, transition metal halides, transition metal alkylates, transition metal alkoxylates, and non-bridged or bridged metallocene compounds of Groups 4 to 6 of the periodic table can be used as such transition metal compounds. In particular, transition metal compounds of Group 4 of the periodic table are preferred. Among these, a carrier-supported metallocene catalyst component belonging to the carrier-supported transition metal complex catalyst components is preferred, and a carrier-supported metallocene catalyst component containing the following components (A-1) to (A-3) is more preferred. (A-1) a transition metal compound of Group 4 of the periodic table having a cyclopentadienyl skeleton, (A-2) at least one compound selected from the group consisting of the following components (a) to (c): (a) organometallic compound, (b) organoaluminum oxy-compounds, and (c) a compound that reacts with component (A-1) to form an ion pair; (A-3) Microparticle carrier.
[0016] Specific examples of the transition metal compound of Group 4 of the periodic table include titanium tetrachloride, dimethyltitanium dichloride, tetrabenzyltitanium, tetrabenzylzirconium, and tetrabutoxytitanium. Furthermore, from the viewpoint of polymerization activity (yield of olefin polymer per 1 g of catalyst) in the polymerization reaction of the catalyst, non-bridged or bridged metallocene compounds are particularly preferred. The metallocene compound is a transition metal compound of Group 4 of the periodic table having a cyclopentadienyl skeleton, and is represented, for example, by the following general formula (III).
[0017] ML d (III) [In general formula (III), M is a transition metal of Group 4 of the periodic table (specifically, zirconium, titanium or hafnium). L is a ligand (group) coordinated to the transition metal, and at least one L is a ligand having a cyclopentadienyl skeleton. L other than the ligand having a cyclopentadienyl skeleton is a hydrocarbon group having 1 to 12 carbon atoms, an alkoxy group, an aryloxy group, a halogen atom, a trialkylsilyl group, -SO3R' (R' is a hydrocarbon group having 1 to 8 carbon atoms which may have a substituent such as a halogen) or a hydrogen atom. d is the valence of the transition metal and indicates the number of L.]
[0018] Specific examples of the ligand having a cyclopentadienyl skeleton include a cyclopentadienyl group, an alkyl-substituted cyclopentadienyl group such as a methylcyclopentadienyl group, a dimethylcyclopentadienyl group, a trimethylcyclopentadienyl group, a tetramethylcyclopentadienyl group, a pentamethylcyclopentadienyl group, an ethylcyclopentadienyl group, a methylethylcyclopentadienyl group, a propylcyclopentadienyl group, a methylpropylcyclopentadienyl group, a butylcyclopentadienyl group, a methylbutylcyclopentadienyl group, or a hexylcyclopentadienyl group, an indenyl group, a 4,5,6,7-tetrahydroindenyl group, or a fluorenyl group. These groups may have a substituent such as a halogen atom or a trialkylsilyl group.
[0019] As the ligand having a cyclopentadienyl skeleton, an alkyl-substituted cyclopentadienyl group is particularly preferred. When the compound represented by the general formula (III) contains two or more groups having a cyclopentadienyl skeleton, the two groups having a cyclopentadienyl skeleton may be bonded via an alkylene group such as ethylene or propylene; an alkylidene group such as isopropylidene or diphenylmethylene; a silylene group; or a substituted silylene group such as a dimethylsilylene group, a diphenylsilylene group, or a methylphenylsilylene group. In addition, it is preferable that the groups having two or more cyclopentadienyl skeletons are the same.
[0020] Specific examples of the hydrocarbon group having 1 to 12 carbon atoms other than the ligand having a cyclopentadienyl skeleton include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, and pentyl; cycloalkyl groups such as cyclopentyl and cyclohexyl; aryl groups such as phenyl and tolyl; and aralkyl groups such as benzyl and neophyl. Specific examples of the alkoxy group include alkoxy groups having 1 to 4 carbon atoms such as methoxy, ethoxy, and butoxy. Specific examples of the aryloxy group include phenoxy. Specific examples of the halogen atom include fluorine, chlorine, bromine, and iodine. Specific examples of -SO3R' include p-toluenesulfonato, methanesulfonato, and trifluoromethanesulfonato. When there are a plurality of ligands other than the ligand having a cyclopentadienyl skeleton, these ligands may be the same or different, and one or more combinations of different ligands may be present.
[0021] The compound represented by general formula (III), for example when the transition metal has a valence of 4, is more specifically represented by the following general formula (III'). MR 1 R 2 R 3 R 4 (III') [In the general formula (III'), M is zirconium, titanium or hafnium. 1R is a group having a cyclopentadienyl skeleton. 2 , R 3 and R 4 are each independently a group having a cyclopentadienyl skeleton, an alkyl group, a cycloalkyl group, an aryl group, an aralkyl group, an alkoxy group, an aryloxy group, a halogen atom, a trialkylsilyl group, -SO3R' (R' is a hydrocarbon group having 1 to 8 carbon atoms which may have a substituent such as a halogen) or a hydrogen atom.
[0022] In particular, the component (A-1) is a compound represented by the general formula (III′): 2 , R 3 and R 4 A transition metal compound in which one of R is a group having a cyclopentadienyl skeleton is preferred. For example, R 1 and R 2 When R is a group having a cyclopentadienyl skeleton, the group having a cyclopentadienyl skeleton may be bonded via an alkylene group, a substituted alkylene group, an alkylidene group, a silylene group, a substituted silylene group, or the like. 3 and R 4 is an alkyl group, a cycloalkyl group, an aryl group, an aralkyl group, an alkoxy group, an aryloxy group, a halogen atom, a trialkylsilyl group, -SO3R', or a hydrogen atom. Specific examples of these groups include the same groups as those listed above for formula (III).
[0023] Specific examples of transition metal compounds in which M is zirconium are given below: bis(indenyl)zirconium dichloride, bis(indenyl)zirconium dibromide, bis(indenyl)zirconium bis(p-toluenesulfonato), bis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, bis(fluorenyl)zirconium dichloride, ethylene bis(indenyl)zirconium dichloride, ethylene bis(indenyl)zirconium dibromide, ethylene bis(indenyl)dimethylzirconium, ethylene bis(indenyl)diphenylzirconium, ethylene bis(indenyl)diphenylzirconium, and ethylene bis(indenyl)zirconium dichloride. 1,3-Dimethylcyclopentadiene (cyclopentadienyl)zirconium monochloride, 1,3-diethyl-2,4-dimethylphenyl ether (cyclopentadienyl)zirconium bis(methanesulfonate), 1,3-diethyl-2,4-dimethylphenyl ether (cyclopentadienyl)zirconium bis(p-toluenesulfonate), 1,3-diethyl-2,4-dimethylphenyl ether (cyclopentadienyl)zirconium bis(trifluoromethane ... Dimethylsilylene bis(cyclopentadienyl)zirconium dichloride, dimethylsilylene bis(methylcyclopentadienyl)zirconium dichloride, dimethylsilylene bis(dimethylcyclopentadienyl)zirconium dichloride, dimethylsilylene bis(trimethylcyclopentadienyl)zirconium dichloride, dimethylsilylene bis(indenyl)zirconium dichloride, dimethylsilylene bis(indenyl)zirconium bis(trifluoromethanesulfonate), rac-dimethylsilylene bis {1-(2-methyl-4,5-acenaphthocyclopentadienyl)}zirconium dichloride, rac-dimethylsilylenebis{1-(2-methyl-4,5-benzoindenyl)}zirconium dichloride, rac-dimethylsilylenebis{1-(2-methyl-4-isopropyl-7-methylindenyl)}zirconium dichloride, rac-dimethylsilylenebis{1-(2-methyl-4-phenylindenyl)}zirconium dichloride, rac-dimethylsilylenebis{1-(2-methylindenyl)}zirconium dichloride,Dimethylsilylene bis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, dimethylsilylene(cyclopentadienyl-fluorenyl)zirconium dichloride, diphenylsilylene bis(indenyl)zirconium dichloride, methylphenylsilylene bis(indenyl)zirconium dichloride, bis(cyclopentadienyl)zirconium dichloride, bis(cyclopentadienyl)zirconium dibromide, bis(cyclopentadienyl)methylzirconium monochloride, bis(cyclopentadienyl)ethylzirconium dichloride zirconium monochloride, bis(cyclopentadienyl)cyclohexylzirconium monochloride, bis(cyclopentadienyl)phenylzirconium monochloride, bis(cyclopentadienyl)benzylzirconium monochloride, bis(cyclopentadienyl)zirconium monochloride monohydride, bis(cyclopentadienyl)methylzirconium monohydride, bis(cyclopentadienyl)dimethylzirconium, bis(cyclopentadienyl)diphenylzirconium, bis(cyclopentadienyl)dibenzylzirconium , bis(cyclopentadienyl)zirconium methoxychloride, bis(cyclopentadienyl)zirconium ethoxychloride, bis(cyclopentadienyl)zirconium bis(methanesulfonate), bis(cyclopentadienyl)zirconium bis(p-toluenesulfonate), bis(cyclopentadienyl)zirconium bis(trifluoromethanesulfonate), bis(methylcyclopentadienyl)zirconium dichloride, bis(dimethylcyclopentadienyl)zirconium dichloride, bis(dimethylcyclopentadiene)zirconium dichloride, bis(dimethylcyclopentadienyl)zirconium bis(trifluoromethanesulfonate), bis(ethylcyclopentadienyl)zirconium dichloride, bis(methylethylcyclopentadienyl)zirconium dichloride, bis(propylcyclopentadienyl)zirconium dichloride, bis(methylpropylcyclopentadienyl)zirconium dichloride, bis(butylcyclopentadienyl)zirconium dichloride, bis(methylbutylcyclopentadienyl)zirconium dichloride,Bis(methylbutylcyclopentadienyl)zirconium bis(methanesulfonate), bis(trimethylcyclopentadienyl)zirconium dichloride, bis(tetramethylcyclopentadienyl)zirconium dichloride, bis(pentamethylcyclopentadienyl)zirconium dichloride, bis(hexylcyclopentadienyl)zirconium dichloride, bis(trimethylsilylcyclopentadienyl)zirconium dichloride, etc.
[0024] In the above examples, di-substituted cyclopentadienyl rings include 1,2- and 1,3-substituted cyclopentadienyl rings, and tri-substituted cyclopentadienyl rings include 1,2,3- and 1,2,4-substituted cyclopentadienyl rings. In addition, alkyl groups such as propyl and butyl include isomers such as n-, i-, sec-, and tert-.
[0025] Also, in the above zirconium compounds, transition metal compounds in which zirconium metal is replaced with titanium metal or hafnium metal can be used.In addition to titanium compounds and hafnium compounds having similar steric structures, as well as bromides and iodides, transition metal compounds as described in, for example, JP-A-3-9913, JP-A-2-131488, JP-A-3-21607, JP-A-3-106907, JP-A-3-188092, JP-A-4-69394, JP-A-4-300887, and International Publication No. 2001 / 27124 can be mentioned.
[0026] Further, examples of the transition metal compound include transition metal compounds represented by the following general formula (IV) as described in JP-A-11-315109.
[0027] [ka]
[0028] [In general formula (IV), M 1 represents a transition metal atom in Groups 4 to 6 of the periodic table. f represents an integer of 1 to 6. R 11 ~R 16R each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group, a heterocyclic compound residue, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group. 11 ~R 16 Two or more of the groups may be linked together to form a ring. When f is 2 or more, R 11 ~R 16 Between multiple units having the same structure, these groups are each independently defined as above. 11 ~R 16 Two of the groups may be linked together (provided that multiple R 11 (e is M 1 X represents a hydrogen atom, a halogen atom, a hydrocarbon group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a boron-containing group, an aluminum-containing group, a phosphorus-containing group, a halogen-containing group, a heterocyclic compound residue, a silicon-containing group, a germanium-containing group, or a tin-containing group. When e is 2 or more, the multiple groups represented by X are each independently defined as above. The multiple groups represented by X may be the same or different, or the multiple groups represented by X may contain one or more combinations of different groups. In addition, the multiple groups represented by X may be bonded to each other to form a ring.] Specific examples of the substituent as X include the groups disclosed in JP-A-11-315109.
[0029] Component (A-2) constituting the carrier-supported transition metal complex catalyst component is at least one compound selected from the group consisting of organometallic compounds (a), organoaluminum oxy compounds (b), and compounds (c) that react with component (A-1) to form an ion pair.
[0030] As the organometallic compound (a), for example, organometallic compounds belonging to Groups 1 and 2, and Groups 12 and 13 of the periodic table, represented by the following general formulas (V), (VI) and (VII), can be used.
[0031] R 5g Al(OR 6 ) h H i X 1 j ···(V) [In general formula (V), R 5 and R 6 each independently represent a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms. X 1 represents a halogen atom. g is a number where 0 < g ≦ 3, h is a number where 0 ≦ h < 3, i is a number where 0 ≦ i < 3, j is a number where 0 ≦ j < 3, and g + h + i + j = 3.] An organoaluminum compound represented by this. As this hydrocarbon group, an alkyl group is preferred. Specific examples of the compound represented by general formula (V) include trimethylaluminum, triethylaluminum, triisobutylaluminum, and diisobutylaluminum hydride.
[0032] M 2 AlR 7 4···(VI) [In general formula (VI), M 2 represents Li, Na, or K, and R 7 represents a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms.] An organometallic complex compound of a Group 1 metal of the periodic table and aluminum represented by this. As the above hydrocarbon group, an alkyl group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms, is preferred. Specific examples of the compound represented by general formula (VI) include LiAl(C2H5)4 and LiAl(C7H 15 )4.
[0033] R 8 R 9 M 3 ···(VII) [In general formula (VII), R 8 and R 9 may be the same as or different from each other and represent a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms. M 3 is Mg, Zn, or Cd.] An organometallic compound of a metal in Group 2 or 12 of the periodic table. The hydrocarbon group is preferably an alkyl group.
[0034] Among the above organometallic compounds, organoaluminum compounds are preferred. The organometallic compounds may be used alone or in combination of two or more.
[0035] As the organoaluminum oxy compound (b), a known aluminoxane can be used. Specifically, for example, at least one of the compounds represented by the following general formulas (VIII) and (IX) can be used.
[0036] [ka]
[0037] [ka]
[0038] [In general formulas (VIII) and (IX), R 21 ~R 24 each independently represents a hydrocarbon group having 1 to 10 carbon atoms, and k and p each independently represent an integer of 2 or greater.
[0039] As the organoaluminum oxy compound (b), there may be mentioned a compound represented by the general formulas (VIII) and (IX), in which R 21 ~R 24Methylaluminoxanes in which k is a methyl group and k and p are 3 or more, preferably 10 or more, are preferably used. A small amount of an organoaluminum compound may be mixed into these aluminoxanes. The organoaluminum oxy compound (b) may be a benzene-insoluble organoaluminum oxy compound as exemplified in JP-A-2-78687. The organoaluminum oxy compounds described in JP-A-2-167305 and the aluminoxanes having two or more alkyl groups as described in JP-A-2-24701 and JP-A-3-103407 are also preferably used.
[0040] Such aluminoxanes can be produced, for example, by the following methods (1) to (3), and are usually obtained as a solution in a hydrocarbon solvent.
[0041] (1) A method in which an organoaluminum compound such as trialkylaluminum is added to a hydrocarbon medium suspension of a compound containing adsorbed water or a salt containing water of crystallization, such as magnesium chloride hydrate, copper sulfate hydrate, aluminum sulfate hydrate, nickel sulfate hydrate, or cerous chloride hydrate, to react the organoaluminum compound with the adsorbed water or water of crystallization. (2) A method in which water, ice or water vapor is directly reacted with an organoaluminum compound such as trialkylaluminum in a medium such as benzene, toluene, ethyl ether or tetrahydrofuran. (3) A method in which an organoaluminum compound such as trialkylaluminum is reacted with an organotin oxide such as dimethyltin oxide or dibutyltin oxide in a medium such as decane, benzene, or toluene.
[0042] The aluminoxane may contain a small amount of an organometallic component. After the solvent or unreacted organoaluminum compound is removed by distillation from the recovered aluminoxane solution, the aluminoxane may be redissolved in a solvent.
[0043] Specific examples of the organoaluminum compound used in preparing the aluminoxane include trialkylaluminums such as trimethylaluminum, triethylaluminum, tripropylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, trisec-butylaluminum, tritert-butylaluminum, tripentylaluminum, trihexylaluminum, trioctylaluminum, and tridecylaluminum; tricycloalkylaluminums such as tricyclohexylaluminum and tricyclooctylaluminum; dialkylaluminum halides such as dimethylaluminum chloride, diethylaluminum chloride, diethylaluminum bromide, and diisobutylaluminum chloride; dialkylaluminum hydrides such as diethylaluminum hydride and diisobutylaluminum hydride; dialkylaluminum alkoxides such as dimethylaluminum methoxide and diethylaluminum ethoxide; and dialkylaluminum aryloxides such as diethylaluminum phenoxide. Among these, trialkylaluminums and tricycloalkylaluminums are preferred.
[0044] Furthermore, isoprenylaluminum represented by the following general formula (X) can also be used as an organoaluminum compound for preparing aluminoxane.
[0045] (i-C4H9) r Al s (C5H 10 ) t (X) [In the general formula (X), r, s, and t are positive numbers, and t≧2r.]
[0046] The organoaluminum compounds for preparing the aluminoxane may be used alone or in combination of two or more.
[0047] Specific examples of the solvent used in preparing the aluminoxane include aromatic hydrocarbons such as benzene, toluene, xylene, cumene, and cymene, aliphatic hydrocarbons such as pentane, hexane, heptane, octane, decane, dodecane, hexadecane, and octadecane, alicyclic hydrocarbons such as cyclopentane, cyclohexane, cyclooctane, and methylcyclopentane, petroleum fractions such as gasoline, kerosene, and diesel, and halides of the above aromatic hydrocarbons, aliphatic hydrocarbons, and alicyclic hydrocarbons, particularly chlorinated and brominated hydrocarbons. In addition, ethers such as ethyl ether and tetrahydrofuran can also be used. Among these, aromatic hydrocarbons are preferred.
[0048] Examples of the compound (c) that reacts with component (A-1) to form an ion pair (hereinafter also referred to as "ionized ionic compound (c)") include Lewis acids, ionic compounds, borane compounds, and carborane compounds, as well as heteropoly compounds and isopoly compounds, described in JP-A-1-501950, JP-A-1-502036, JP-A-3-179005, JP-A-3-179006, JP-A-3-207703, JP-A-3-207704, U.S. Patent No. 5,321,106, and the like. The fact that the ionizing ionic compound (c) acts as an activator for metallocene catalysts is disclosed, for example, in Japanese Patent No. 5295501. The ionizing ionic compound (c) may be used alone or in combination of two or more kinds.
[0049] The organometallic compound (a), the organoaluminum oxy-compound (b), and the ionizing ionic compound (c) that can be used as component (A-2) have been described above. However, it is preferable to use, as component (A-2), the organoaluminum oxy-compound (b) alone or a combination of the organoaluminum compound (a) and the organoaluminum oxy-compound (b).
[0050] The particulate carrier (A-3) may be an inorganic carrier made of an inorganic material or an organic carrier made of an organic material. Examples of the inorganic carrier include inorganic metal oxide carriers such as SiO2, Al2O3, MgO, ZrO2, TiO2, B2O3, CaO, ZnO, BaO, ThO2, and mixtures containing two or more of these (e.g., SiO2-MgO, SiO2-Al2O3, SiO2-TiO2, SiO2-V2O5, SiO2-Cr2O3, SiO2-TiO2-MgO), and inorganic chloride carriers such as MgCl2, MgBr2, MnCl2, and MnBr2. Clay, clay minerals that are components of clay, ion-exchangeable layered compounds, and the like may also be used as the inorganic carrier. Examples of the organic carrier include organic polymer carriers such as polyethylene, polypropylene, poly-1-butene, poly-4-methyl-1-pentene, and styrene-divinylbenzene copolymers.
[0051] The inorganic carrier has an average particle size of preferably 1 to 300 μm, more preferably 3 to 200 μm. If necessary, such a carrier is fired at 100 to 1000° C., preferably 150 to 700° C. before use.
[0052] The inorganic chloride may be used as it is, or may be used after being pulverized by a ball mill or a vibration mill.In addition, the inorganic chloride may be dissolved in a solvent such as alcohol and then precipitated into fine particles by a precipitating agent.
[0053] A carrier using clay is usually composed of a clay mineral as a main component. A carrier using an ion-exchangeable layered compound has a crystal structure in which the planes formed by ionic bonds or the like are stacked in parallel with each other with weak bonding force, and the ions contained therein are exchangeable. Most clay minerals are ion-exchangeable layered compounds. These clays, clay minerals, and ion-exchangeable layered compounds are not limited to natural products, and artificial synthetic products can also be used. Examples of clays, clay minerals, and ion-exchangeable layered compounds include clays, clay minerals, and ionic crystalline compounds having layered crystal structures such as hexagonal close packing type, antimony type, CdCl2 type, and CdI2 type. Examples of such clays and clay minerals include kaolin, bentonite, kibushi clay, gairome clay, allophane, hisinger stone, pyrophyllite, unmo group, montmorillonite group, vermiculite, ryokudeite group, palygorskite, kaolinite, nacrite, dickite, and halloysite. Examples of ion-exchangeable layered compounds include crystalline acid salts of polyvalent metals such as α-Zr(HAsO4)2·H2O, α-Zr(HPO4)2, α-Zr(KPO4)2·3H2O, α-Ti(HPO4)2, α-Ti(HAsO4)2·H2O, α-Sn(HPO4)2·H2O, γ-Zr(HPO4)2, γ-Ti(HPO4)2, and γ-Ti(NH4PO4)2·H2O. It is also preferable to subject clay and clay minerals to chemical treatment. As chemical treatment, any of surface treatments that remove impurities attached to the surface and treatments that affect the crystal structure of clay can be used. Specific examples of chemical treatments include acid treatment, alkali treatment, salt treatment, and organic matter treatment.
[0054] The ion-exchangeable layered compound may be a layered compound in which the space between layers is expanded by utilizing the ion exchangeability and exchanging the exchangeable ions between layers with other large bulky ions. Such bulky ions play a role of supporting the layered structure and are usually called pillars. The introduction of another substance between layers of a layered compound in this way is called intercalation. Examples of guest compounds for intercalation include cationic inorganic compounds such as TiCl4 and ZrCl4, metal alkoxides such as Ti(OR″4, Zr(OR″4, PO(OR″3, B(OR″3) (each R″ independently represents a hydrocarbon group, etc.), [Al 13 O4(OH) 24 ] 7+ , [Zr4(OH) 14 ] 2+ , [Fe3O(OCOCH3)6] + Metal hydroxide ions such as these can be used alone or in combination of two or more of these compounds. When these compounds are intercalated, polymers obtained by hydrolysis of metal alkoxides such as Si(OR″4), Al(OR″3, Ge(OR″4) (R″ each independently represents a hydrocarbon group, etc.), and colloidal inorganic compounds such as SiO2 can also be used. Examples of pillars include oxides produced by intercalating the above-mentioned metal hydroxide ions between layers and then dehydrating them with heat. Among these, preferred are clays or clay minerals, and particularly preferred are montmorillonite, vermiculite, pectolite, taeniolite, and synthetic mica.
[0055] The organic carrier may be a granular or particulate solid having a particle size in the range of 1 to 300 μm. Specific examples of the polymer forming the organic carrier include, as exemplified above, (co)polymers produced mainly from α-olefins having 3 to 14 carbon atoms, such as ethylene, propylene, 1-butene, and 4-methyl-1-pentene, or (co)polymers produced mainly from vinylcyclohexane and styrene, and modified products thereof.
[0056] Also, a solid component obtained by insolubilizing the above-described component (A-2) by the method described in JP-A-11-140113, JP-A-2000-38410, JP-A-2000-95810, WO 2010 / 55652, etc. can be used as the fine particle support (A-3). In this case, contact with the component (A-2) in the preparation method of the support-supported metallocene catalyst component described below is not essential.
[0057] A method for preparing a carrier-supported metallocene catalyst component preferably used as the solid catalyst component (A) for olefin polymerization is described below. This carrier-supported metallocene catalyst can be prepared by mixing and contacting components (A-1) to (A-3). The components may be contacted in any order. Each of the components (A-1) to (A-3), or at least one of the components (a) to (c) as component (A-2), may be used in multiple separate contacts.
[0058] In the preparation of the carrier-supported metallocene catalyst component, it is preferable to use an inert hydrocarbon solvent, specifically, aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, kerosene, etc., alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, etc., aromatic hydrocarbons such as benzene, toluene, xylene, etc., halogenated hydrocarbons such as ethylene chloride, chlorobenzene, dichloromethane, etc., or mixtures thereof.
[0059] When preparing the carrier-supported metallocene catalyst component, the transition metal compound (A-1) is used in an amount of usually 0.001 to 1.0 millimoles, preferably 0.005 to 0.5 millimoles, per gram of the particulate carrier (A-3) calculated as transition metal atoms. The organoaluminum oxy compound (b) is used in an amount of usually 0.1 to 100 millimoles, preferably 0.5 to 20 millimoles, calculated as aluminum atoms. When an organoaluminum compound is used, the organoaluminum compound is used in an amount of usually 0.001 to 1000 millimoles, preferably 2 to 500 millimoles, per gram of the particulate carrier (A-3).
[0060] The temperature when the above components are mixed and contacted is usually −50 to 150° C., preferably −20 to 120° C., and the contact time is 1 to 1000 minutes, preferably 5 to 600 minutes.
[0061] The thus obtained carrier-supported metallocene catalyst component contains the transition metal compound (A-1) in an amount of preferably about 5×10 in terms of transition metal atom per gram of the fine particle carrier (A-3). -6 ~10 -3 moles, more preferably 10 -5 ~3×10 -4 The amount of the organoaluminum oxy-compound (b) is preferably about 10 moles in terms of aluminum atom per gram of the fine particle carrier (A-3). -3 ~10 -1 moles, more preferably 2×10 -3 ~5×10 -2 It is carried on in molar amounts.
[0062] The solid catalyst component (A) for olefin polymerization may be a prepolymerized catalyst component in which a monomer for preparing an olefin polymer is prepolymerized. One form of the prepolymerized catalyst component contains the solid catalyst component for olefin polymerization and, if necessary, an olefin polymer produced by prepolymerization. A preferred form of the prepolymerized catalyst contains a transition metal compound (A-1), a component (A-2), a fine particle support (A-3), and, if necessary, an olefin polymer (D) produced by prepolymerization. As a method for preparing the prepolymerization catalyst, for example, in the presence of a solid catalyst component obtained by mixing and contacting components (A-1) to (A-3) in an inert hydrocarbon solvent or in a medium containing a monomer for preparing an olefin polymer, a small amount of a monomer for forming an olefin polymer is prepolymerized. As mentioned above, the order of contacting components (A-1) to (A-3) is not particularly limited. In addition, at least one of these components may be contacted in multiple batches. Specific examples of the inert hydrocarbon solvent used in the preparation of the prepolymerized catalyst include the same inert hydrocarbon solvents as those used in the preparation of the carrier-supported metallocene catalyst described above.
[0063] As a monomer for preparing an olefin polymer used in the prepolymerization, at least one of ethylene, propylene, and an olefin having a carbon number of 4 to 20 can be used. The olefin for the prepolymerization preferably has the following composition (A). Composition (A): Ethylene: 100 to 0 mol%, Propylene: 0 to 49 mol %, and α-olefins having 4 or more carbon atoms: 0 to 100 mol %. Furthermore, the following composition (B) can be mentioned as a more preferable composition, the following composition (C) as an even more preferable composition, and the following composition (D) as an especially preferable composition. ·Composition (B): Ethylene: 100 to 0 mol%, Propylene: 0 to 20 mol %, and α-Olefins having 4 or more carbon atoms: 0 to 100 mol %. ·Composition (C): Ethylene: 100 to 20 mol%, Propylene: 0 to 20 mol %, and α-olefins having 4 or more carbon atoms: 0 to 80 mol %. ·Composition (D): Ethylene: 100 to 20 mol %, and α-olefins having 4 or more carbon atoms: 0 to 80 mol %. (In each of the above compositions, the sum of the mole percent of ethylene, the mole percent of propylene, and the mole percent of olefins having 4 or more carbon atoms is 100%).
[0064] Specific examples of α-olefins having 4 to 20 carbon atoms include 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc. Furthermore, as monomers to be copolymerized with α-olefins, cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, 2-methyl-1,4:5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene, styrene, vinylcyclohexane, dienes, etc. can also be used.
[0065] In preparing the prepolymerization catalyst, the transition metal compound (A-1) is used in an amount of usually 0.001 to 1.0 mmol, preferably 0.005 to 0.5 mmol, per gram of the particulate carrier (A-3) calculated as transition metal atoms. The organoaluminum oxy compound (b) is used in an amount of usually 0.1 to 100 mmol, preferably 0.5 to 20 mmol, per gram of the particulate carrier (A-3) calculated as aluminum atoms.
[0066] The prepolymerized catalyst obtained as described above contains the transition metal compound (A-1) in an amount of preferably about 5×10 in terms of transition metal atom per gram of the fine particle support (A-3). -6 ~10 -3 moles, more preferably 10 -5 ~3×10 -4 The organoaluminum oxy compound (b) is supported in an amount of preferably about 10 moles in terms of aluminum atom per gram of the fine particle support (A-3). -3 ~10 -1 moles, more preferably 2×10 -3 ~5×10 -2 The olefin polymer (D) produced by prepolymerization is desirably supported on the fine particle support (A-3) in an amount of about 0.1 to 500 g, preferably 0.3 to 300 g, and particularly preferably 1 to 100 g.
[0067] In addition, the solid catalyst component (A) for olefin polymerization may contain other components useful for polymerization in addition to the above-described components. In addition, the carrier-supported metallocene catalyst component may optionally contain a surfactant other than those represented by the general formulae (I) and (II) during catalyst synthesis or prepolymerization, as necessary.
[0068] [Polyoxyethylene alkylamine compound (B)] The polyoxyethylene alkylamine compound [component (B)] is a compound represented by the following general formula (I).
[0069] [ka]
[0070] [In general formula (I), R is a hydrocarbon group having 1 to 30 carbon atoms, and m and n are each independently an integer of 1 or more.]
[0071] The hydrocarbon group represented by R in the general formula (I) may be saturated or unsaturated. The hydrocarbon group may be linear, branched, or cyclic, or may have two or more of these structures. The hydrocarbon group may be an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, or a group having at least two of these groups. Examples of the aliphatic hydrocarbon group include an alkyl group and an alkenyl group. Specific examples of preferred hydrocarbon groups include alkyl groups or alkenyl groups such as a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, a lauryl group, and an oleoyl group. Other examples include cycloalkyl groups such as a cyclopentyl group and a cyclohexyl group; aryl groups such as a phenyl group and a tolyl group; and aralkyl groups such as a benzyl group and a neophyl group. Among these, an alkyl group having 8 to 18 carbon atoms is preferred.
[0072] In the general formula (I), m and n are each an integer of 1 or more. m and n are each independently preferably 1 to 5. m+n is preferably 2 to 10.
[0073] Specific examples of the polyoxyethylene alkylamine compound (B) represented by the general formula (I) include lauryl diethanolamine, stearyl diethanolamine, polyoxyethylene octylamine, polyoxyethylene decylamine, polyoxyethylene laurylamine, polyoxyethylene stearylamine, polyoxyethylene coconut oil alkylamine, polyoxyethylene tallow amine, and polyoxyethylene hydrogenated tallow amine. Among these, lauryl diethanolamine, stearyl diethanolamine, polyoxyethylene laurylamine, polyoxyethylene stearylamine, and polyoxyethylene coconut oil alkylamine are preferred.
[0074] As the component (B), at least one compound selected from the group consisting of compounds represented by general formula (I) can be used.
[0075] [Polyalkylene oxide block compound (C)] The polyalkylene oxide block compound [component (C)] is a compound represented by the following general formula (II).
[0076] [ka]
[0077] The compound represented by the general formula (II) is generally used as a nonionic surfactant. The average chain length of the portion consisting of oxyethylene units represented by -CH2CH2O- in the molecular structure represented by the general formula (II), a and c, are each independently selected from the range of 1 to 20, preferably 1 to 10. The average chain length of the portion consisting of oxypropylene units represented by -CH2CH(CH3)O- in the molecular structure represented by the general formula (II), b, is selected from the range of 1 to 50, preferably 3 to 45, more preferably 4 to 40.
[0078] [Production of olefin polymers] The process for producing an olefin polymer of the present invention comprises a step of (co)polymerizing one or more olefins selected from the group consisting of ethylene and α-olefins having 3 to 20 carbon atoms in a polymerization vessel in the presence of the above-described component (A) (solid catalyst component for olefin polymerization), component (B) (polyoxyethylene alkylamine compound), and component (C) (polyalkylene oxide block compound). In the present invention, the term "(co)polymerization" is used in a sense that includes both polymerization and copolymerization. In the present invention, "polymerization" and "polymer" may be used in a sense that includes not only "homopolymerization" and "homopolymer", but also "copolymerization" and "copolymer", respectively.
[0079] In (co)polymerization, the method of supplying components (A) to (C) to a polymerization vessel is arbitrary and is not particularly limited. Components (A) to (C) may be added individually to a polymerization vessel in any order. Alternatively, a mixture of two of components (A) to (C) that have been previously mixed and contacted may be added to a polymerization vessel in any order, and the remaining components may be added to a polymerization vessel. Alternatively, a mixture of components (A) to (C) that have been previously mixed and contacted may be added to a polymerization vessel. Furthermore, two or more of these addition methods may be combined. Component (A) may be added to a polymerization vessel as a prepolymerized solid catalyst component.
[0080] A preferred method for adding components (A) to (C) to a polymerization vessel is the following method in which components (B) and (C) are used as a mixture a. (1) Component (A) and mixture a are prepared separately and then added to a polymerization vessel. (2) A method in which component (A) is brought into contact with a mixture a, and the resulting preparation a is supplied to a polymerization reactor. (3) A method in which component (A) is contacted with mixture a to obtain preparation a, which is then fed to a polymerization reactor, and mixture a is then fed to the polymerization reactor. The order in which component (A) and mixture a are fed to the polymerization vessel in method (1) is not particularly limited. They may be fed to the polymerization vessel simultaneously, or one of them may be fed to the polymerization vessel first and then the other. In the method (3), the order of supplying the preparation a and the mixture a to the polymerization vessel is not particularly limited. They may be supplied to the polymerization vessel at the same time, or one of them may be supplied to the polymerization vessel first and then the other. It is preferable to supply the preparation a to the polymerization vessel first and then supply the mixture a. In this case, the supply of the mixture a to the polymerization vessel after the supply of the preparation a to the polymerization vessel can be performed at least one of the following timings: before the start of polymerization in the polymerization vessel, at the start of polymerization, and during the polymerization reaction. In the methods (1) to (3), when the component (A) and the mixture a are supplied to the polymerization vessel, at least one of them may be supplied to the polymerization vessel in multiple batches. As the component (A) in the above methods (1) to (3), a prepolymerized catalyst component obtained by prepolymerizing a monomer for olefin polymerization in the presence of a solid catalyst component for olefin polymerization may be used.
[0081] [Solid catalysts for olefin polymerization] The solid catalyst component (A) for olefin polymerization can be used for olefin (co)polymerization by supplying it to a polymerization reactor as a solid catalyst for olefin polymerization either alone or in a form containing the solid catalyst component (A) for olefin polymerization together with other components. The solid catalyst for olefin polymerization may contain at least one of a polyoxyethylene alkylamine compound (B) and a polyalkylene oxide block compound (C) used in combination therewith as a stabilizer for stabilizing the operation of a production apparatus. The solid catalyst for olefin polymerization may be a prepolymerized catalyst prepared through prepolymerization of a monomer for olefin polymerization. The solid catalyst for olefin polymerization can be prepared by contacting the solid catalyst component for olefin polymerization (A) with at least one of the polyoxyethylene alkylamine compound (B) and the polyalkylene oxide block compound (C). When the metallocene catalyst component containing the above-mentioned components (A-1) to (A-3) is used as a solid catalyst component for olefin polymerization, at least one of the polyoxyethylene alkylamine compound (B) and the polyalkylene oxide block compound (C) may be added at any stage during the production of the metallocene catalyst component using these components according to the above-mentioned production method. The timing of adding at least one of the components (B) and (C) is not particularly limited. In addition, when a prepolymerization catalyst component using a metallocene catalyst component is used as the solid catalyst component (A) for olefin polymerization, at least one of the above-mentioned components (B) and (C) may be added when producing the prepolymerization catalyst component according to the above-mentioned production method. The timing of adding at least one of these components (B) and (C) is not particularly limited. It is preferable to obtain a prepolymerization catalyst containing these components (B) and (C) by contacting the components (B) and (C) with the prepolymerization catalyst obtained by using the solid catalyst component for olefin polymerization prepared using the components (A-1) to (A-3) and a monomer for prepolymerization. For example, a solid catalyst component for olefin polymerization is prepared using component (A-1), component (b) (organoaluminum oxy compound) as component (A-2), and component (A-3), and then component (a) (organometallic compound) is added as component (A-2) to the solid catalyst component and prepolymerized. The prepolymerized catalyst obtained is then contacted with components (B) and (C), whereby a solid catalyst for olefin polymerization containing these components (B) and (C) can be prepared as a prepolymerization catalyst. The solid catalyst for olefin polymerization or the prepolymerization catalyst may be fed to the polymerization vessel in several batches.
[0082] By using the above-mentioned component (B) in combination with component (C), fouling of the inside of the polymerization vessel, such as the walls of the polymerization vessel and the stirring blades, can be effectively prevented, and further improvements in the operational stability and polymerization activity of the production apparatus can be achieved. The present inventors presume that the reason for such an effect is that component (B) and component (C) form an interactor, which makes it possible to achieve stable operation of the production apparatus and further improve polymerization activity while maintaining the above-mentioned antifouling effect.
[0083] The compounding ratio (mass ratio) of component (B) to component (C) can be preferably selected from the range of component (B):component (C)=100:1 to 100:100. This compounding ratio is more preferably selected from the range of 100:1 to 100:50, and particularly preferably selected from the range of 100:1 to 100:30. The blending ratio (mass ratio) of component (B) to component (A) is more preferably selected from the range of component (A):component (B)=100:0.01 to 100:50, and particularly preferably selected from the range of 100:0.01 to 100:10.
[0084] The polymerization can be carried out in any of suspension, solution or gas phase, and is preferably carried out in suspension or gas phase by slurry polymerization or gas phase polymerization.Specific examples of the inert hydrocarbon medium used in slurry polymerization include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, kerosene, etc.; alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, etc.; halogenated hydrocarbons such as ethylene chloride, chlorobenzene, dichloromethane, etc., or mixtures thereof.Among these, aliphatic hydrocarbons and alicyclic hydrocarbons are preferred.
[0085] The polymerization temperature is usually -50 to 150°C, preferably 0 to 100°C, in the case of slurry polymerization, and usually 0 to 120°C, preferably 20 to 100°C, in the case of gas phase polymerization. The polymerization pressure is usually normal pressure to 10 MPa gauge pressure, preferably normal pressure to 5 MPa gauge pressure. The polymerization reaction can be carried out by any of a batch method, a semi-continuous method, and a continuous method.
[0086] The polymerization can be carried out in two or more stages with different reaction conditions. The molecular weight of the resulting olefin polymer can be adjusted by making hydrogen present in the polymerization system or by changing the polymerization temperature.
[0087] At least one selected from ethylene and α-olefins having 3 to 20 carbon atoms is used as a raw material for polymerization. Specific examples of the α-olefin include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. These can be used alone or in combination of two or more. In addition to ethylene and α-olefins having 3 to 20 carbon atoms, other copolymerization monomers may be used in combination for copolymerization. Examples of copolymerization monomers include cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, and 2-methyl-1,4:5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene. Styrene, vinylcyclohexane, and dienes can also be used.
[0088] As the olefin as a raw material for polymerization, an olefin having any of the compositions (A) to (D) exemplified above for the preliminary polymerization can be used. Furthermore, in the present invention, it is preferable to produce an ethylene-based polymer having ethylene as the main monomer. As the ethylene-based polymer, a (co)polymer containing 50 mol % or more of an ethylene component and, if necessary, containing an α-olefin component having 4 to 10 carbon atoms is preferable.
[0089] In the polymerization, the olefin polymerization catalyst (A) is used in an amount of usually 10 -8 ~10 -3 Molar, preferably 10 -7 ~10 -4The organoaluminum oxy compound (A-2) is desirably used in an amount of usually 10 to 500 mol, preferably 20 to 200 mol, per mol of transition metal atom in the transition metal compound (A-1) calculated as aluminum atom. EXAMPLES
[0090] The present invention will be described in more detail with reference to the following examples, although the present invention is not limited to the description of the following examples.
[0091] [Stabilizer] The stabilizer (B) [component (B)] used in the examples and comparative examples is as follows: "B-1": Lauryldiethanolamine [Electrostripper (registered trademark) EA, manufactured by Kao Corporation] "B-2": Stearyldiethanolamine [CAS number 10213-78-2, manufactured by Tokyo Chemical Industry Co., Ltd.] "B-3": polyoxyalkylene alkylamine compound [Amit (registered trademark) 102, manufactured by Kao Corporation] (the analysis results of the types and composition ratios of the compounds contained are disclosed in Table 1 of the patent document (JP 2019-157019 A)). "B-4": polyoxyalkylene alkylamine compound [Amit (registered trademark) 105, manufactured by Kao Corporation] "B-5": Alkyldiethanolamine compound [Atomer (registered trademark) 163, manufactured by Croda Japan Co., Ltd.] (The analysis results of the types and composition ratios of the compounds contained are disclosed in Table 1 of the patent document (JP 2019-157019 A).)
[0092] "Polyalkylene oxide block compound" The polyalkylene oxide block compounds [component (C)] used in the examples and comparative examples are as follows: "C-1": polyoxyethylene polyoxypropylene block compound [ADEKA Pluronic (registered trademark) L-71, manufactured by ADEKA Corporation] "C-2": polyoxyethylene polyoxypropylene block compound [ADEKA Pluronic (registered trademark) L-72, manufactured by ADEKA Corporation] "C'-1": polyalkylene oxide alkyl ether compound [EMULGEN (registered trademark) 108, manufactured by Kao Corporation]
[0093] [Preparation Example 1] (Preparation of solid catalyst component (X-1)) A 270 L reactor equipped with a stirrer was used, and silica gel (manufactured by Fuji Silysia Chemical Ltd., average particle size 70 μm, specific surface area 340 m) was added under a nitrogen atmosphere. 2 / g, pore volume 1.3cm 3 10 kg of methylaluminoxane (100 g, dried at 250°C for 10 hours) was suspended in 77 L of toluene and then cooled to 0-5°C. While maintaining the temperature in the system at 0-5°C, 19.4 L of a toluene solution of methylaluminoxane (3.5 mol / L in terms of Al atoms) was dropped into this suspension over 30 minutes. After contacting each added component for 30 minutes, the temperature in the system was raised to 95°C over 1.5 hours, and then contacted at 93-97°C for 4 hours. After that, the temperature was lowered to room temperature, the supernatant was removed by decantation, and the mixture was washed twice with toluene to obtain a total of 115 L of toluene slurry of a solid carrier carrying methylaluminoxane. A part of this slurry was sampled and analyzed, and the solid concentration was 123 g / L. Of the obtained slurry, 12.2 L (1.50 kg as solid content) was charged into a reactor with an inner volume of 114 L equipped with a stirrer under a nitrogen atmosphere, and toluene was added to make the total amount 28 L. Next, a solution in which 23.5 g (54.2 mmol in terms of Zr atom) of bis(1,3-n-butylmethylcyclopentadienyl)zirconium dichloride was dissolved in 5.0 L of toluene was pumped into the reactor and contacted for 1 hour at a system temperature of 20 to 25°C. The supernatant liquid was removed by decantation and washed three times with hexane. Then, hexane was further added to make the total amount 30 L, and a hexane slurry of the solid catalyst component (X-1) was obtained.
[0094] [Preparation Example 2] (Preparation of prepolymerized solid catalyst component (XP-1)) 30L of hexane slurry of the solid catalyst component (X-1) obtained in Preparation Example 1 was cooled to 10°C, and 2.89mol of diisobutylaluminum hydride (DiBAl-H) was added thereto. While maintaining the temperature in the system at 10-15°C, ethylene was continuously fed into the system under normal pressure for several minutes, and then 70ml of 1-hexene was added. Then, ethylene feeding was started at 1.46kg / h, and prepolymerization was performed at a system temperature of 32-37°C. 70ml of 1-hexene was added five times in total every 30 minutes after the start of prepolymerization, and when the ethylene feeding reached 4.37kg 180 minutes after the start of prepolymerization, the ethylene feeding was stopped. Then, the supernatant liquid was removed by decantation, and washed four times with hexane. Then, hexane was further added to make the total amount 30L, and a hexane slurry of the prepolymerized solid catalyst component (XP-1) was obtained. Next, the hexane slurry was introduced into a 43 L agitator-equipped evaporator under nitrogen atmosphere, and the pressure was reduced to -68 kPaG over about 60 minutes. When the pressure reached -68 kPaG, the mixture was vacuum-dried for about 4.3 hours to remove hexane and volatile matters in the prepolymerized catalyst component. The pressure was further reduced to -100 kPaG, and when the pressure reached -100 kPaG, the mixture was vacuum-dried for 8 hours to obtain 6.20 kg of a prepolymerized solid catalyst component (XP-1).
[0095] [Example 1] (Polymerization evaluation (i): Evaluation of autoclave wall condition during polymerization) 500 ml of n-heptane was charged into a 1 L stainless steel autoclave that had been thoroughly purged with nitrogen, and the system was purged with ethylene. 10 ml of 1-hexene and 250 mg of the prepolymerized solid catalyst component (XP-1) obtained in Preparation Example 2 were added, and the temperature was raised to 55°C. It took about 10 minutes from the addition of the prepolymerized solid catalyst component (XP-1) until the temperature reached 55°C. Then, a mixture of 5.00 mg of lauryldiethanolamine (B-1) as component (B) and 0.50 mg of Adeka Pluronic L-71 (C-1) as component (C) [component (B-1): component (C) = 100:10 (mass ratio)] was diluted with 5 ml of toluene and added. Then, 200 mg of the prepolymerized solid catalyst component (XP-1) was added, and the temperature in the system was raised to 73°C. Next, polymerization was started by introducing ethylene, and the pressure was reduced to 8.0 kg / cm while continuously supplying ethylene. 2 The polymerization was carried out for 90 minutes while maintaining the temperature at -G. After the polymerization was completed, the pressure was released, the polymer was removed, and the condition of the autoclave was checked. No adhesion of the polymer to the vessel wall or the stirring blades of the autoclave was observed.
[0096] (Polymerization evaluation (ii): Polymerization activity evaluation) 500 ml of n-heptane was charged into a 1L stainless steel autoclave that had been thoroughly purged with nitrogen, and the system was purged with ethylene. 20 ml of 1-hexene and 0.06 ml of a decane solution of triisobutylaluminum (1.0 mol / L) were added and held at room temperature for 5 minutes. Then, 5.00 mg of lauryldiethanolamine (B-1) as component (B) and 0.50 mg of Adeka Pluronic L-71 (C-1) as component (C) [component (B-1): component (C) = 100:10 (mass ratio)] were mixed and diluted with 5 ml of toluene and added. Then, 180 mg of prepolymerized solid catalyst component (XP-1) was added and the temperature in the system was raised to 73 ° C. Next, polymerization was started by introducing ethylene, and the pressure was increased to 8.0 kg / cm while continuously supplying ethylene. 2The polymerization was carried out for 90 minutes while keeping the temperature at -G. After the polymerization was completed, the pressure was released, and the polymer was filtered, washed, and dried at 80°C under reduced pressure for 10 hours to obtain 95.8 g of polymer. The amount of component (B-1) relative to the polymer yield (g) was 52 ppm (mass basis), and the polymer yield per 1 g of catalyst (polymerization activity) was 532 (g-PE / g-cat).
[0097] [Examples 2 to 8 and Reference Examples 1 to 7] Polymerization evaluation (i) and polymerization evaluation (ii) were carried out in the same manner as in Example 1, except that the type of stabilizer [component (B)] and the type and amount of polyalkylene oxide block compound [component (C)] were changed as shown in Table 1. The results are shown in Table 1.
[0098] [Table 1]
[0099] As is clear from Table 1, in Examples 1 to 3 in which component (B-1) and component (C-1) were used, adhesion of the polymer to the autoclave vessel wall and stirring blades was suppressed, and the polymerization activity was higher than that of Reference Example 1 in which only component (B-1) was used, Reference Example 2 in which only component (C-1) was used, and Reference Example 3 in which component (B-1) and polyalkylene oxide alkyl ether (C'-1) were used. That is, in Examples 1 to 3, olefin polymers could be produced stably with higher polymerization activity than in Reference Examples 1 to 3. Moreover, in Example 4, in which the components (B-1) and (C-2) were used, the polymerization activity was higher than that in Reference Example 1. In Examples 5 to 8, in which components (B-3) to (B-5) and component (C-1) were used instead of component (B-1), the polymerization activity was higher than that in Reference Examples 4 to 7, in which only components (B-2) to (B-5) were used.
[0100] [Preparation Example 3] (Preparation of prepolymerized solid catalyst component (XP-2)) In a reactor equipped with a stirrer having an internal volume of 200 ml, 10.0 g of the prepolymerized solid catalyst component (XP-1) obtained in Preparation Example 2 was charged under a nitrogen atmosphere, and hexane was added so that the total amount became 50 ml. Next, the temperature in the system was raised to 35°C, and then a mixture of 100.0 mg of lauryl diethanolamine (B-1) as component (B) and 0.0 mg of Adeka Pluronic L-71 (C-1) as component (C) [component (B-1): component (C) = 100: 10 (mass ratio)] was diluted with 5 ml of toluene and charged, and the mixture was contacted at 32 to 37°C for 2 hours to obtain a hexane slurry of the prepolymerized solid catalyst component (XP-2). This hexane slurry was transferred to a glass Schlenk flask having an internal volume of 100 ml, and hexane was distilled off under reduced pressure at 25°C to obtain 10.1 g of the prepolymerized solid catalyst component (XP-2).
[0101] [Example 9] (Polymerization evaluation (i): Evaluation of autoclave wall condition during polymerization) 500 ml of n-heptane was charged into a 1 L stainless steel autoclave that had been thoroughly purged with nitrogen, the system was purged with ethylene, 10 ml of 1-hexene and 250 mg of the prepolymerized solid catalyst component (XP-2) obtained in Preparation Example 3 were added, and the temperature was raised to 55°C. It took about 10 minutes from the addition of the prepolymerized solid catalyst component (XP-2) until the temperature reached 55°C. Then, 200 mg of the prepolymerized solid catalyst component (XP-2) was further added, and the temperature in the system was raised to 73°C. Next, polymerization was started by introducing ethylene, and the pressure was increased to 8.0 kg / cm while continuously supplying ethylene. 2 The polymerization was carried out for 90 minutes while maintaining the temperature at -G. After the polymerization was completed, the pressure was released, the polymer was removed, and the condition of the autoclave was checked. No adhesion of the polymer to the vessel wall or the stirring blades of the autoclave was observed.
[0102] (Polymerization evaluation (ii): Polymerization activity evaluation) 500 ml of n-heptane was charged into a 1 L stainless steel autoclave that had been thoroughly purged with nitrogen, and the system was purged with ethylene. 20 ml of 1-hexene and 0.06 ml of a decane solution of triisobutylaluminum (1.0 mol / L) were then added and held at room temperature for 5 minutes. Then, 180 mg of prepolymerized solid catalyst component (XP-2) was added and the temperature in the system was raised to 73°C. Next, polymerization was started by introducing ethylene, and the pressure was increased to 8.0 kg / cm while continuously supplying ethylene. 2 The polymerization was carried out for 90 minutes while maintaining the temperature at -G. After the polymerization was completed, the pressure was released, and the polymer was filtered, washed, and dried at 80°C under reduced pressure for 10 hours to obtain 119.2 g of polymer. The polymer yield per 1 g of catalyst (polymerization activity) was 662 (g-PE / g-cat).
[0103] [Preparation Example 4] (Preparation of prepolymerized solid catalyst component (XP-3)) In a 200 ml reactor equipped with a stirrer, 10.0 g of the prepolymerized solid catalyst component (XP-1) obtained in Preparation Example 2 was charged under a nitrogen atmosphere, and hexane was added so that the total amount became 50 ml. Next, the temperature in the system was raised to 35°C, and then 100.0 mg of lauryldiethanolamine (B-1) was diluted with 5 ml of toluene as component (B) and charged, and the mixture was contacted at 32 to 37°C for 2 hours to obtain a hexane slurry of the prepolymerized solid catalyst component (XP-3). This hexane slurry was transferred to a 100 ml glass Schlenk flask, and hexane was distilled off under reduced pressure at 25°C to obtain 10.1 g of the prepolymerized solid catalyst component (XP-3).
[0104] [Reference example 7] (Polymerization evaluation (i): Evaluation of autoclave wall condition during polymerization) 500 ml of n-heptane was charged into a 1 L stainless steel autoclave that had been thoroughly purged with nitrogen, the system was purged with ethylene, 10 ml of 1-hexene and 250 mg of the prepolymerized solid catalyst component (XP-3) obtained in Preparation Example 4 were added, and the temperature was raised to 55°C. It took about 10 minutes from the addition of the prepolymerized solid catalyst component (XP-3) until the temperature reached 55°C. Then, 200 mg of the prepolymerized solid catalyst component (XP-3) was further added, and the temperature in the system was raised to 73°C. Next, polymerization was started by introducing ethylene, and the pressure was increased to 8.0 kg / cm while continuously supplying ethylene. 2 The polymerization was carried out for 90 minutes while maintaining the temperature at -G. After the polymerization was completed, the pressure was released, the polymer was removed, and the condition of the autoclave was checked. No adhesion of the polymer to the vessel wall or the stirring blades of the autoclave was observed.
[0105] (Polymerization evaluation (ii): Polymerization activity evaluation) 500 ml of n-heptane was charged into a 1 L stainless steel autoclave that had been thoroughly purged with nitrogen, and the system was purged with ethylene. 20 ml of 1-hexene and 0.06 ml of a decane solution of triisobutylaluminum (1.0 mol / L) were then added and held at room temperature for 5 minutes. Then, 180 mg of prepolymerized solid catalyst component (XP-3) was added and the temperature in the system was raised to 73°C. Next, polymerization was started by introducing ethylene, and the pressure was increased to 8.0 kg / cm while continuously supplying ethylene. 2 The polymerization was carried out for 90 minutes while maintaining the temperature at -G. After the polymerization was completed, the pressure was released, and the polymer was filtered, washed, and dried at 80°C under reduced pressure for 10 hours to obtain 110.8 g of polymer. The polymer yield per 1 g of catalyst (polymerization activity) was 616 (g-PE / g-cat).
[0106] [Preparation Example 5] (Preparation of prepolymerized solid catalyst component (XP-4)) In a 200 ml reactor equipped with a stirrer, 10.0 g of the prepolymerized solid catalyst component (XP-1) obtained in Preparation Example 2 was charged under a nitrogen atmosphere, and hexane was added so that the total amount became 50 ml. Next, the temperature in the system was raised to 35°C, and then 100.0 mg of Adeka Pluronic L-71 (C-1) was diluted with 5 ml of toluene as component (C) and charged, and the mixture was allowed to contact for 2 hours at 32 to 37°C to obtain a hexane slurry of the prepolymerized solid catalyst component (XP-4). This hexane slurry was transferred to a 100 ml glass Schlenk flask, and hexane was distilled off under reduced pressure at 25°C to obtain 10.1 g of the prepolymerized solid catalyst component (XP-4).
[0107] [Reference example 8] (Polymerization evaluation (i): Evaluation of autoclave wall condition during polymerization) 500 ml of n-heptane was charged into a 1 L stainless steel autoclave that had been thoroughly purged with nitrogen, the system was purged with ethylene, 10 ml of 1-hexene and 250 mg of the prepolymerized solid catalyst component (XP-4) obtained in Preparation Example 5 were added, and the temperature was raised to 55°C. It took about 10 minutes from the addition of the prepolymerized solid catalyst component (XP-4) until the temperature reached 55°C. Then, 200 mg of the prepolymerized solid catalyst component (XP-4) was further added, and the temperature in the system was raised to 73°C. Next, polymerization was started by introducing ethylene, and the pressure was increased to 8.0 kg / cm while continuously supplying ethylene. 2 The polymerization was carried out for 90 minutes while maintaining the temperature at -G. After the polymerization was completed, the pressure was released, the polymer was removed, and the condition of the autoclave was checked. No adhesion of the polymer to the vessel wall or the stirring blades of the autoclave was observed.
[0108] (Polymerization evaluation (ii): Polymerization activity evaluation) 500 ml of n-heptane was charged into a 1 L stainless steel autoclave that had been thoroughly purged with nitrogen, and the system was purged with ethylene. 20 ml of 1-hexene and 0.06 ml of a decane solution of triisobutylaluminum (1.0 mol / L) were then added and held at room temperature for 5 minutes. Then, 180 mg of prepolymerized solid catalyst component (XP-4) was added and the temperature in the system was raised to 73°C. Next, polymerization was started by introducing ethylene, and the pressure was increased to 8.0 kg / cm while continuously supplying ethylene. 2 The polymerization was carried out for 90 minutes while maintaining the temperature at -G. After the polymerization was completed, the pressure was released, and the polymer was filtered, washed, and dried at 80°C under reduced pressure for 10 hours to obtain 113.8 g of polymer. The polymer yield per 1 g of catalyst (polymerization activity) was 632 (g-PE / g-cat).
[0109] [Example 10] (Polymerization evaluation (iii): Operability evaluation by gas phase polymerization) Copolymerization of ethylene and 1-hexene was carried out using a gas-phase fluidized bed polymerization apparatus. The polymerization pressure was 1.7 MPaG, and the polymerization temperature was 80°C. The prepolymerized solid catalyst component (XP-2) prepared in Preparation Example 3 was fed into the polymerization reactor at 4.2 g / hr. A mixture of lauryldiethanolamine (B-1) as component (B) and Adeka Pluronic L-71 (C-1) as component (C) in a mass ratio of 100:10 was fed into the circulation gas line so that (B-1) was present in an amount of 30 ppm (mass basis) relative to the mass of the polymer. The gas composition in the gas-phase polymerization reactor was ethylene partial pressure = 1.0 MPa, hydrogen / ethylene = 4.8 x 10 -4 Ethylene, hydrogen, 1-hexene and isopentane were continuously fed so that the molar ratio of 1-hexene / ethylene was 0.022, and a polymer was produced at a rate of 6.0 kg / hr. The residence time was 4 hours. The polymer density at this time was 916 kg / m 3 The melt flow rate was 3.8 g / 10 min. The melt flow rate was measured at 190° C. under a load of 2.16 kg in accordance with ASTM D1238-65T. The operation was carried out for 48 hours under the above conditions, and no heat spots were observed in any parts such as the polymerization vessel or piping, and stable polymerization was possible. The polymer yield per gram of catalyst (polymerization activity) was 1429 (g-PE / g-cat).
[0110] [Reference example 9] (Polymerization evaluation (iii): Operability evaluation by gas phase polymerization) Copolymerization of ethylene and 1-hexene was carried out using a gas-phase fluidized bed polymerization apparatus. The polymerization pressure was 1.7 MPaG, and the polymerization temperature was 80°C. The prepolymerized solid catalyst component (XP-3) prepared in Preparation Example 4 was fed into the polymerization reactor at 4.8 g / hr. Lauryldiethanolamine (B-1) as component (B) was fed into the circulation gas line so that it was present in an amount of 30 ppm (mass basis) as (B-1) relative to the mass of the polymer. The gas composition in the gas-phase polymerization reactor was ethylene partial pressure = 1.0 MPa, hydrogen / ethylene = 4.8 x 10 -4 Ethylene, hydrogen, 1-hexene and isopentane were continuously fed so that the molar ratio of 1-hexene / ethylene was 0.022, and a polymer was produced at a rate of 6.0 kg / hr. The residence time was 4 hours. The polymer density at this time was 916 kg / m 3 The melt flow rate was 3.8 g / 10 min. The melt flow rate was measured at 190° C. under a load of 2.16 kg in accordance with ASTM D1238-65T. The operation was carried out for 48 hours under the above conditions, and no heat spots were observed in any parts such as the polymerization vessel or piping, and stable polymerization was possible. The polymer yield per gram of catalyst (polymerization activity) was 1250 (g-PE / g-cat). [Industrial Applicability]
[0111] According to the present invention, there can be provided a method for producing an olefin polymer which is capable of preventing fouling of the inside of a polymerization vessel, such as the walls of the polymerization vessel or the stirring blades, and which can achieve further improvements in the operational stability and polymerization activity of the production apparatus. The present invention greatly contributes to improving the productivity of olefin polymers using a catalyst.
Claims
1. In the presence of (A) a solid catalyst component for olefin polymerization, (B) a polyoxyethylene alkylamine compound represented by the following general formula (I), and (C) a polyalkylene oxide block compound represented by the following general formula (II), A process for producing an olefin polymer, comprising (co)polymerizing ethylene and one or more olefins selected from the group consisting of α-olefins having from 3 to 20 carbon atoms in a polymerization vessel. 【Chemistry 1】 [In the above general formula (I), R is a hydrocarbon group having 1 to 30 carbon atoms, and m and n are each independently an integer of 1 or more.] 【Chemistry 2】 [In the above general formula (II), a represents 1 to 20, b represents 1 to 50, and c represents 1 to 20.]
2. 2. The process for producing an olefin polymer according to claim 1, wherein the mixture of components (B) and (C) and component (A) are added separately to a polymerization vessel.
3. 2. The process for producing an olefin polymer according to claim 1, wherein a preparation obtained by contacting a mixture of the components (B) and (C) with the component (A) is supplied to a polymerization vessel.
4. 2. The method for producing an olefin polymer according to claim 1, wherein a preparation obtained by contacting a mixture of components (B) and (C) with component (A) is supplied to a polymerization vessel, and further, a mixture of components (B) and (C) is supplied to the polymerization vessel.
5. The process for producing an olefin polymer according to any one of claims 1 to 4, wherein the (co)polymerization of olefins is carried out in a suspension or in a gas phase.
6. Component (A) is (A-1) a compound of a transition metal of Group 4 of the periodic table having a cyclopentadienyl skeleton; (A-2) at least one compound selected from the group consisting of (a) organometallic compounds, (b) organoaluminum oxy compounds, and (c) compounds that react with component (A-1) to form an ion pair; (A-3) a fine particle carrier; The method for producing an olefin polymer according to any one of claims 1 to 5, comprising:
Citation Information
Patent Citations
Improvement in fluidity of polymeric powder
JP2000313718A
Slurry polymerization of olefin
JP2000327707A
Production of prepolymerization catalyst for olefin polymerization
JP2001048912A
Slurry polymerization method for olefin
JP2004262992A
Process for producing olefin polymer
JP2014019825A